Chemical composition and bioactivities of the essential oil of Coreopsis tinctoria and Chrysanthemum morifolium - Zhong-Rong Jiang; Ting Zhang; Ling-Bo Ji; Lei Wu; Hong-Hui Dong; Guo-Liang Zhao; Hong-Qian Shentu; Bao-Jiang He; Tian-Xiao Li (International Journal of Food Properties)
This study was aiming at the differences in the aroma, flavor compounds, and bioactivities of essential oil of Coreopsis tinctoria flower (CTFEO) and essential oil of Chrysanthemum morifolium flower (CMFEO). Both essential oils were extracted by steam distillation. Their flavor compositions were determined by GC-MS and the antioxidant, antibacterial, and anti-inflammatory activities were also evaluated. It was found that CTFEO possessed a special medicinal herb odor, which was obviously stronger than those of CMFEO. A preferred condition for steam distillation was flower powder–water ratio of 7.5:100 and extraction for more than 3.0 h. Interestingly, the main flavor compounds of CTFEO were determined as D-limonene (34.54%), cis-carveol (5.49%), trans-α-bergamotene (4.44%), and α-pinene (3.90%), which were quite different from those of CMFEO. CTFEO showed better antioxidant activities with IC50 value of 121.4 ± 9.8 μg/mL than those of CMFEO. It also exhibited stronger antibacterial effects than those of CMFEO, with minimal inhibitory concentrations (MICs) ranging from 0.183 to 1.412 mg/mL against six strains of bacteria. Moreover, CTFEO was also found to exhibit strong anti-inflammatory effects that reduced the LPS-induced RAW 264.7 cell mRNA expression of the cytokines IL-1β, IL-6, and TNF-α at a concentration of 10.0 μg/mL. All these results suggest that the aroma, flavor compounds, and bioactivities of the two essential oils were quite different and they could be used as tea, drink, and food additive in the food industry for further development.